The Parenteral Vitamin C Improves Sepsis and Sepsis-Induced Multiple Organ Dysfunction Syndrome via Preventing Cellular Immunosuppression - Yu-Lei Gao; Bin Lu; Jian-Hua Zhai; Yan-Cun Liu; Hai-Xia Qi; Ying Yao; Yan-Fen Chai; Song-Tao Shou (Mediators of Inflammation)
Cellular immunosuppression appears to be involved in sepsis and sepsis-induced multiple organ dysfunction syndrome (MODS). Recent evidence showed that parenteral vitamin C (Vit C) had the ability to attenuate sepsis and sepsis-induced MODS. Herein, we investigated the impact of parenteral Vit C on cellular immunosuppression and the therapeutic value in sepsis. Using cecal ligation and puncture (CLP), sepsis was induced in WT and Gulo−/− mice followed with 200 mg/Kg parenteral Vit C administration. The immunologic functions of CD4+CD25+ regulatory T cells (Tregs) and CD4+CD25− T cells, as well as the organ functions, were determined. Administration of parenteral Vit C per se markedly improved the outcome of sepsis and sepsis-induced MODS of WT and Gulo−/− mice. The negative immunoregulation of Tregs was inhibited, mainly including inhibiting the expression of forkhead helix transcription factor- (Foxp-) 3, cytotoxic T lymphocyte associated antigen- (CTLA-) 4, membrane associated transforming growth factor-β (TGF-βm+), and the secretion of inhibitory cytokines [including TGF-β and interleukin- (IL-) 10], as well as CD4+ T cells-mediated cellular immunosuppression which was improved by parenteral Vit C in WT and Gulo−/− septic mice. These results suggested that parenteral Vit C has the ability to improve the outcome of sepsis and sepsis-induced MODS and is associated with improvement in cellular immunosuppression.